2013
DOI: 10.1159/000355936
|View full text |Cite
|
Sign up to set email alerts
|

Should We Measure Fetal Omphalocele Diameter for Prediction of Perinatal Outcome?

Abstract: Objective: To evaluate the fetal omphalocele diameter/abdominal circumference ratio (OD/AC) as a predictor of adverse perinatal outcome. Methods: Analysis involving 47 singleton pregnancies with fetal omphalocele, normal karyotype and absence of other major abnormalities. The OD/AC ratio was determined antenatally by ultrasound and the best cutoff for the prediction of neonatal death was determined by receiver operating characteristic curve analysis. Additional secondary outcomes included need for oral intubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
(46 reference statements)
1
18
1
Order By: Relevance
“…In line with our finding, Kleinrouweler et al also found a decreasing OC/AC ratio with increasing GA, which resulted in different cut‐offs per GA . Kiyora et al and Montero et al, however, found no difference in ratios per GA. The latter study used fetal growth parameters (AC, femur length, and head circumference), which remained relatively constant throughout gestation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with our finding, Kleinrouweler et al also found a decreasing OC/AC ratio with increasing GA, which resulted in different cut‐offs per GA . Kiyora et al and Montero et al, however, found no difference in ratios per GA. The latter study used fetal growth parameters (AC, femur length, and head circumference), which remained relatively constant throughout gestation.…”
Section: Discussionsupporting
confidence: 91%
“…The latter study used fetal growth parameters (AC, femur length, and head circumference), which remained relatively constant throughout gestation. The suggested ratios resulted in a lower predictive value for the prediction of postnatal closure (AUC 0.67–0.72) than the OC/AC ratio in our study (AUC 0.96–0.98), as did all ratios including omphalocele diameter instead of circumference . Additional research should make clear whether correction for GA could result in a constant cut‐off throughout gestation, without negatively affecting the predictive value.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The latter informs them in depth about the postnatal outcome [15,17,18]. While prenatal indicators of a successful primary closure are known, so far there are no guidelines to individualize counseling about postnatal prognosis [4,8,15,19,20,21,22,23,24]. Consequently, the full spectrum of postnatal morbidity is discussed.…”
Section: Introductionmentioning
confidence: 99%